Analysis of pregnant women coagulopathy biomarker factors on covid-19 infection in the fetal - Suryani Manurung (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Of the 62 babies born, 20 (32 percent) were infected with covid-19, the average age of premature birth.Purpose: To analyze the relationship between coagulopathy biomarker factors in pregnant women infected with covid-19 and the incidence of covid-19 infection in newborns.Method: Cross-sectional with the retrospective method. The inclusion criteria were babies born from mothers infected with covid-19, and newborns aged 0-28 days. The number of samples is 145. The sampling technique is purposive sampling. The data collection instrument is an observation sheet. Data were collected for 12 weeks from hospital medical records. Analysis of chi-square test data and independent t-test.Results: Participants were young adults as much as 86 (61.4 percent). Gestational age-based delivery was premature as much as 55 (37.9 percent). The gestational age range at delivery is 28 weeks to 41 weeks, gestational age when infected with covid-19 trimester III a gestational age range is from 29 weeks to 41 weeks. Coagulopathy biomarker values experienced There were 140 abnormal D-dimers with a range of >500 (96.6 percent). All babies are born of mothers infected with covid-19, less than 0 days after birth, 39 were infected (27.1 percent) were infected with covid-19 at <0 days. D-dimer coagulopathy biomarkers exist a significant relationship (p-value < 0.05) against infection of newborns from the inside Womb.Conclusion: Coagulopathy biomarker factors in pregnant women are related to the occurrence of babies infected with covid-19. Where the incidence of infection in newborns has occurred since zero days born.